The Use of Virtual Reality in Radiology Education: Review Article Year of Publication 2010 - 2022 - Ardi Soesilo Wibowo; Edy Cahyono; Sutikno Sutikno; Dyah Rini Indriyanti; Bambang Subali; Ellianawati Ellianawati (International Conference on Science, Education, and Technology, 2022)
Background: Advancement in the healthcare sector, the complexity of health problems and healthcare system become an additional burden for healthcare workers who have incompetence along with professional education of healthcare workers, specifically in radiology education. Virtual reality has great potential in educational learning tool development to encounter various challenges in future radiology education. Objective: To determine the scope of virtual reality and its effectiveness as an educational learning tool in radiology education. Methods: A literature review was carried out to explore articles related with application of virtual reality in radiology education by adjusting various search terms: "virtual reality", and "radiology"/ "radiography" / “x-ray” / “radiology technologist” / “education”. Articles were selected based on the inclusion and exclusion criteria that have been previously assigned. The timeframe for the literature search was restricted from 2010 to 2022. screening process. Results: Screening process were applied to search across database. Twelve articles were identified related with the application of virtual reality in radiology education. Application of virtual reality had been implemented in several sub-fields of radiology education, consist of three articles from conventional radiography, two articles from general diagnostic radiology, four articles from interventional radiology, two articles from radiological anatomy, and an article from ultrasonography. Conclusion: The application of virtual reality has been used in several sub-fields of radiology education. Almost all studies showed positive responses on application VR in radiology education. The development of virtual reality as radiology educational learning tools were needed further particularly in several sub-fields that have not been implemented.